Inventory Application Design for Optimizing Business Processes for MSMEs Nyong Group Yogyakarta - Putri Taqwa Prasetyaningrum; Albert Yakobus Chandra; Irfan Pratama (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Nyong Group is one of the Micro, Small and Medium Enterprises (MSME) located in Sleman, Yogyakarta. Nyong group has several business units, namely nyong shoes and care Yogya, shoes and care Cilacap, nyong donuts, and nyong stalls (food, snacks and chili sauce). The problems by IbM partners include; First, (1) There is no Point of Sales application that uses inventory to meet the needs of the production process or is sold again, (2) Not yet has this Inventory covering raw materials, in-process goods, and goods so (finished goods). The output targets in this program are (1) the application of point of sales applications for recording sales transactions, (2) Adding an inventory application to the created point of sales applications. The service program is carried out in 2 (two) forms; First, (1) design of a point of sales application for Nyong Group's sales transactions. Second, making an inventory application to be able to determine whether to record goods based on arrival time or the amount of stock you can determine to record goods based on arrival time or stock amount. The implementation of this program is designed in four stages of activity, namely: (1) Coordination and preparation stage (2) Design stage (3) Science and technology implementation stage (4) Evaluation and refinement stage.